2019
DOI: 10.1016/j.bpj.2019.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Sphingomyelin Stereoisomers Reveal That Homophilic Interactions Cause Nanodomain Formation

Abstract: The structure of threo-SSMs 5 and 6 in Figure 1 was mistakenly drawn for the configuration of a 2-NH group, where a C-N bound should have been drawn with a bold line as shown below. FIGURE 1 Chemical structures of sphingomyelin (D-erythro-SSM, SSM), SSM enantiomer (L-erythro-SSM, ent-SSM), SSM diastereomer (L-threo-SSM, threo-SSM), and their deuterated analogs. (Corrected)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
29
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(32 citation statements)
references
References 0 publications
3
29
0
Order By: Relevance
“…The lateral packing of L‐ threo ‐SM, which occurs as a common impurity in semisynthetic SMs, is slightly weaker than that of natural SM; by differential scanning calorimetry (DSC), L‐ threo SM with a stearoyl chain exhibited a slightly lower main phase transition temperature ( T m ; 44.1‐44.2°C) as compared with that of native SM ( T m ; 44.7‐44.9°C) (Figure ) . These data suggested that compared with the L‐ threo configuration, the D‐ erythro configuration plays a certain role in the stabilization of SM‐SM interactions via appropriate hydrogen bonding.…”
Section: Sphingomyelin Diastereomers and Enantiomermentioning
confidence: 98%
See 4 more Smart Citations
“…The lateral packing of L‐ threo ‐SM, which occurs as a common impurity in semisynthetic SMs, is slightly weaker than that of natural SM; by differential scanning calorimetry (DSC), L‐ threo SM with a stearoyl chain exhibited a slightly lower main phase transition temperature ( T m ; 44.1‐44.2°C) as compared with that of native SM ( T m ; 44.7‐44.9°C) (Figure ) . These data suggested that compared with the L‐ threo configuration, the D‐ erythro configuration plays a certain role in the stabilization of SM‐SM interactions via appropriate hydrogen bonding.…”
Section: Sphingomyelin Diastereomers and Enantiomermentioning
confidence: 98%
“…Differential scanning calorimetry thermograms of native stearoyl sphingomyelin (SM) (A); its enantiomer, ent‐ SM (B); and diastereomer, threo‐ SM (C) . Reprinted with permission from Biophysical Journal, 2018, 115, 1530‐1540.…”
Section: Sphingomyelin Diastereomers and Enantiomermentioning
confidence: 99%
See 3 more Smart Citations